2006
DOI: 10.1007/s10633-006-9007-z
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography and electro-oculogram abnormalities in X-linked retinitis pigmentosa

Abstract: The OCT and EOG were demonstrated to be useful methods to identify the minimal alterations in carriers of X-linked retinitis pigmentosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
2
6
1
Order By: Relevance
“…Previous qualitative OCT assessments have reported retinal layer thinning in studies consisting of 2 carriers (Jacobson et al, 1997) and 5 carriers (Vingolo et al, 2006), in agreement with our findings, however in another study of 3 carriers, retinal thickness was observed to be normal (Genead et al, 2010). The finding of thinning of the outer retinal layers in XLRP carriers is consistent with reports of retinal thinning in RP (Hood et al, 2009), as well as thinning of the outer nuclear layer found in a canine model of XLRP carriers (Beltran et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous qualitative OCT assessments have reported retinal layer thinning in studies consisting of 2 carriers (Jacobson et al, 1997) and 5 carriers (Vingolo et al, 2006), in agreement with our findings, however in another study of 3 carriers, retinal thickness was observed to be normal (Genead et al, 2010). The finding of thinning of the outer retinal layers in XLRP carriers is consistent with reports of retinal thinning in RP (Hood et al, 2009), as well as thinning of the outer nuclear layer found in a canine model of XLRP carriers (Beltran et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…An abnormal radial pattern on fundus autofluorescence imaging was found in some subjects, which had some correspondence with areas of visual field loss (Wegscheider et al, 2004). Evidence of reduced thickness of the neurosensory retina and increased outer layer reflectivity has been noted from OCT imaging (Jacobson et al, 1997; Vingolo et al, 2006). …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many previous studies have detailed the prevalence of abnormal fundus photography, 1,2 vitreous fluorophotometry, 3 infrared (IR) reflectance images, 1,2 electroretinographic (ERG), 4,5 psychophysical 6 and flicker-fusion 7 findings in such carriers. More recently, several studies have investigated XLRP carriers with advanced devices, including FAF, 8 multifocal ERG 9 and OCT 10,11 to reveal clinical phenotypes of XLRP. Most XLRP carriers can be identified on the basis of fundus findings and ERG changes; however, 10-30% of carriers show no abnormal ERG or fundus finding.…”
Section: Introductionmentioning
confidence: 99%
“…In evaluating the correlation between the macular thickness and EOG, Vingolo et al 31 evaluated the correlations between OCT and EOG alterations in patients with X-linked RP. They found that the OCT morphology was abnormal in carriers and affected males but not in unaffected females.…”
Section: Figurementioning
confidence: 99%